2020
DOI: 10.3390/toxins12060352
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-Bonded Membranes Do Not Influence Markers of Oxidative Stress in Hemodialysis Patients with Homozygous Glutathione Transferase M1 Gene Deletion

Abstract: Background: Increased oxidative stress is a hallmark of end-stage renal disease. Hemodialysis (HD) patients lacking glutathione transferase M1 (GSTM1) enzyme activity exhibit enhanced oxidative DNA damage and higher mortality rate than those with active GSTM1 enzyme. To our knowledge, this is the first study to use the vitamin E-bonded membranes (VEM) in patients with homozygous GSTM1 gene deletion, and we aimed to determine the effect of VEM on oxidative and inflammatory status in HD patients with homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a multicenter RCT conducted with two parallel groups of 94 patients on HD, theerythropoiesis-stimulating agent resistance index was decreased in the vitamin E-modified membrane group compared with the low-flux synthetic dialyzer group [52]. However, no significant change in the superoxide dismutase or C-reactive protein level or erythropoietin resistance index was observed in another RCT conducted with 80 patients with GSTM1-null genotypes on HD with vitamin E-modified membrane [53]. A systematic review and meta-analysis of 60 studies confirmed that vitamin E-modified membranes significantly decreased the concentrations of IL-6 (MW: 23,718 Da), thiobarbituric acidreactive substances (MW: 144 Da), and plasma and red blood cell malonylaldehyde (MW: 72 Da), but not those of other oxidizing agents, such as NOx (MW: 30-42 Da) in plasma [54].…”
Section: Vitamin E-modified Membranesmentioning
confidence: 95%
“…In a multicenter RCT conducted with two parallel groups of 94 patients on HD, theerythropoiesis-stimulating agent resistance index was decreased in the vitamin E-modified membrane group compared with the low-flux synthetic dialyzer group [52]. However, no significant change in the superoxide dismutase or C-reactive protein level or erythropoietin resistance index was observed in another RCT conducted with 80 patients with GSTM1-null genotypes on HD with vitamin E-modified membrane [53]. A systematic review and meta-analysis of 60 studies confirmed that vitamin E-modified membranes significantly decreased the concentrations of IL-6 (MW: 23,718 Da), thiobarbituric acidreactive substances (MW: 144 Da), and plasma and red blood cell malonylaldehyde (MW: 72 Da), but not those of other oxidizing agents, such as NOx (MW: 30-42 Da) in plasma [54].…”
Section: Vitamin E-modified Membranesmentioning
confidence: 95%
“…Improvements in dialysis membranes and techniques to remove medium-high molecular weight uremic toxins without a significant albumin loss were shown by expanded hemodialysis (HDx), a dialysis modality in which diffusion and convection are combined inside a hollow-fiber dialyzer containing a medium-cut-off (MCO) high-retention-onset membrane [9]. In contrast, vitamin E-bonded membranes showed no benefit in decreasing by-products of oxidative stress and inflammation in dialysis patients lacking glutathione transferase M1 enzyme activity [10]. A paradigm shift from conventional dialysis therapies was represented by binding competitor-augmented hemodialysis.…”
mentioning
confidence: 99%